Essential Oil from the Leaves of the Dwarf Cashew Tree (Anacardium occidentale L.) in the Amazon Savannah: Physicochemical and Antioxidant Properties as a Food Preservative - Maria Clarisnete de Oliveira Moura; Esther Morais da Silva Assuncão; Salatiel Silva Barbosa; Edu Istarley Lourenço Tenente; Alessandro Pereira de Souza; Rajá Vidya Moreira dos Santos; Ana Paula Folmer Correa; Laura Adriane de Moraes Pinto; Amélia Carlos Tuler; Daniela Cavalcante dos Santos Campos; Marcos Jose Salgado Vital; Antonio Alves de Melo Filho; et al. (Foods)
Anacardium occidentale, known as cashew tree, is widely used in the Amazon. This study aimed to evaluate the chemical composition, as well as the biological, physicochemical, antioxidant, and acceptability properties, of the essential oil (EO) extracted from the leaves of the dwarf cashew tree (EOLC) from the Amazonian savanna. The EO was obtained by hydrodistillation from fresh and frozen leaves, with the frozen sample selected due to its higher yield. The components of the EOLC were identified by GC-MS. Antioxidant activity was assessed using DPPH and ABTS radicals, with values of 1.96 µmol Trolox mL−1 and 1.41 mM, respectively. Total phenolic content was determined by the Folin–Ciocalteu method. Antibacterial activity was evaluated by agar diffusion and minimum inhibitory concentration (MIC) methods, and toxicity was assessed with Artemia salina L. The physicochemical properties analyzed included density, refractive index, viscosity, and solubility. Terpinolene was identified as the major compound (80.21%). The EOLC exhibited antioxidant capacity, stronger antibacterial action against Gram-positive bacteria, moderate toxicity, and appropriate physicochemical characteristics. The 0.05% concentration was the most accepted in the sensory evaluation, standing out as a promising natural alternative for application in meat products. These findings highlight the potential of EOLC as a natural food preservative and a source of bioactive compounds, with promising applications in various food matrices.